Living heritage in the historic urban landscape: a case study of the Grand Parade Market - Wilson, Wendy M (School of Architecture, Planning and Geomatics, 2021)
This study examines the long-established bi-weekly market held on Cape Town's Grand Parade to see if it constitutes living heritage. If it does, how is it connected with the urban landscape it inhabits, and how might it be acknowledged or safeguarded? Heritage practice in South Africa has long focused on the fabric of the historic built environment (not on the people using it or the uses to which it is put) with conservation methods tailored to that end. The importance of living heritage—or intangible cultural heritage—is increasingly accepted, particularly as a form of redress for the imbalance caused by the prioritisation of coloniser history. There is a growing sense of urgency, driven by those whose living heritage has been overlooked or ignored, to address this. In this study, I combine on-the-ground analysis of today's Wednesday/Saturday market drawn from interviews with traders, with a deep reading of various official and academic archives. This is interpreted through the most recent theoretical thinking regarding living heritage, together with the international charters, national laws and local policies that apply to the real world of Cape Town today. I determine that the market is, indeed, living heritage, and that it is important to recognise it is such. I argue that the heritage binary of intangible and tangible represents a false dichotomy, and that it is essential to consider heritage as a whole, with living heritage being indivisible from the urban landscape in which it exists. However, I identify the potential pitfalls that formal protection might bring to a living, dynamic system, and find that the significance values of tangible and living heritage require different actions to conserve and safeguard them. I show how, while the will to identify and acknowledge South Africa's living heritage has been expressed at the highest policy levels, the ensuing legislation, implementation policies and working practices of heritage practitioners are insufficient to deliver on this. I suggest that, to reflect this better in our management of heritage resources, a more trans-disciplinary approach is needed, one with processes and methodologies that accommodate diversity in the interpretation of cultural value and emphasise stakeholder involvement.